On proximity focal congested sets in i – topological proximity spaces. Issue 5 (4th July 2022) - Al Talkany, Yiezi K.; Al-Swidi, Luay A.
Abstract: In this research, we gave new types of sets on the i – topological proximity space, which depend on both focal nested sets and focal closure concept. We have used names Pf - congested, Pf - uncongested, CPC - congested, Pf C - congested and CPf - congested set of these new concepts. The relations between them and their transport will also be highlighted by a special type of functions.